2020
DOI: 10.1055/s-0040-1712104
|View full text |Cite
|
Sign up to set email alerts
|

A Framework for Coordination between Obstetric and Pediatric Providers in Public Health Emergencies: Lessons Learned from the Zika Outbreak in the United States, 2015 to 2017

Abstract: Emergency response to emerging threats with the potential for vertical transmission, such as the 2015 to 2017 response to Zika virus, presents unique clinical challenges that underscore the need for better communication and care coordination between obstetric and pediatric providers to promote optimal health for women and infants. Published guidelines for routine maternal-infant care during the perinatal period, and models for transitions of care in various health care settings are available, but no broad fram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Leeb et al ( 13 ) proposed a new coordination framework and strategy to improve nursing coordination and communication in PHE. This framework involved the collection and transmission of key information, communication paths and transfer methods across touch points.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Leeb et al ( 13 ) proposed a new coordination framework and strategy to improve nursing coordination and communication in PHE. This framework involved the collection and transmission of key information, communication paths and transfer methods across touch points.…”
Section: Related Workmentioning
confidence: 99%
“…The research results indicated that this framework could effectively address the nursing coordination. Long term and multidisciplinary management could be achieved ( 13 ). Baines et al ( 14 ) selected COVID-19 in 2020 as a research case to study the ethical adjustment problems that occurred during and after PHE.…”
Section: Related Workmentioning
confidence: 99%
“…Leeb and coworkers report a framework for coordination between obstetric and pediatric provides in their combined response to the Zika outbreak in the U.S from 2015 to 2017 (23). They provide a framework to help coordinate the care of pregnant women and their infants exposed to congenital threats.…”
mentioning
confidence: 99%
“…Leeb et al also address creating information transfer pathways, standardized protocols and procedures, and clear handoffs that include verbal and written components that capture the quantity and detail of shared information (23). Triage and transfer lists are helpful for caregivers, unit managers, and administrators in sending and receiving facilities.…”
mentioning
confidence: 99%